Association of alcohol-induced loss of consciousness and overall alcohol consumption with risk for dementia - Kivimäki, M; Singh-Manoux, A; Batty, GD; Sabia, S; Sommerlad, A; Floud, S; Jokela, M; Vahtera, J; Beydoun, MA; Suominen, SB; Koskinen, A; Väänänen, A; et al. (American Medical Association, 2020)
Importance Evidence on alcohol consumption as a risk factor for dementia usually relates to overall consumption. The role of alcohol-induced loss of consciousness is uncertain.